Hubungan Antara Gaya Hidup Hedonisme dengan Tingkat Harga Diri pada Mahasiswa di Semarang - Leni Alfiyah; Wigyo Susanto; Dwi Heppy Rochmawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study investigates the relationship between hedonistic lifestyle tendencies and self-esteem among students at the Faculty of Nursing, Sultan Agung Islamic University in Semarang. Using a quantitative correlational design, the study analyzed data from 115 respondents to determine the strength and significance of the association between the two variables. The findings demonstrate a significant and strong positive correlation (p = 0.000; r = 0.764), indicating that students with higher hedonistic tendencies tend to report higher levels of self-esteem. This pattern suggests that a considerable portion of students develop a sense of self-worth based on external reinforcement such as social acceptance, peer approval, and recognition from their environment. Although such externally driven self-esteem may enhance confidence temporarily, it may also be unstable because it relies heavily on fluctuating social dynamics. To foster healthier psychological development, students are encouraged to cultivate internal sources of self-worth, while educational institutions are advised to provide programs on healthy lifestyle management, financial literacy, and mental health support. Future researchers are recommended to incorporate longitudinal approaches and include additional variables such as digital platform usage, family support, and peer influence to broaden the generalizability of the findings.